The chemistry and photochemistry of Ru(II) bipyridyl carbonyl complexes incorporated in Nafion - Jermyn, Adrienne (Trinity College (Dublin, Ireland). School of Chemistry, 1991)
The chemical reactions of bis(bpy)carbonylruthenium complexes, catalysts for the water gas shift reaction, have been investigated under mild conditions in Nafion, an ionic polymer. Chemical and photochemical reactions performed under alkaline, aqueous or atmospheric conditions were of particular interest. A variety of techniques have been used to investigate the reactions occurring. These include Infra-red and Ultra-violet spectroscopy. The Nafion matrix is ideally suited to these techniques for bis(bpy)carbonylcomplexes because of the absence of absorption bands in the UV/V is spectrum and the carbonyl region of the IR spectrum. It is also chemically inert. It is possible to prepare and incorporate the complexes into Nation. Reactions are confined within an inert matrix and therefore the species involved in the water gas shift reaction catalysed by [Ru(bpy)2(CO)CI]+ have been formed in-situ and subsequently characterised by spectroscopic methods. Nucleophilic attack of OH- on [Ru(bpy)2(CO2)2+ affords [Ru(bpy)2(CO)(COOH)]+ which exists as an equilibrium mixture with [Ru(bpy)2(CO)2]2+ and [Ru(bpy)2(CO)( COO-)]+ in alkaline media depending on pH. This undergoes some decarboxylation to partially give the hydride [Ru(bpy)2(CO)H]+ which further reacts in water to afford [Ru(bpy)2(CO)(H2O)]2+. This in turn exists in equilibrium with [Ru(bpy)2(CO)(OH)]+. The coordinated H2O of [Ru(bpy)2(CO)(H20)]2+ readily undergoes substitution by CO to yield [Ru(bpy)2(CO)2]2 +. Bpy = 2,2’ - Bipyridyl
Keywords: Chemistry, M.Sc.; M.Sc. Trinity College Dublin